2010
DOI: 10.1007/s10354-010-0761-x
|View full text |Cite
|
Sign up to set email alerts
|

The vagal immune reflex: a blessing from above

Abstract: The innate immune response is activated upon recognition of infection or injury. A tight regulation of this inflammatory response is vital to ensure that it does not spin out of control and becomes harmful to the host. Recently, a neural circuit has been identified that controls the inflammatory response in a reflex-like manner. This circuit involves the vagus nerve which is able to sense inflammation and to respond to it by releasing acetylcholine which, through an interaction with immune cells, dampens the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…In the lungs, pharmacological α7nAChR stimulation correlated with reduced lipopolysaccharide (LPS)-induced neutrophil recruitment [61]. Collectively, these studies suggest that either by electrical or chemical intervention, this infl ammatory refl ex pathway can be modifi ed to modulate the infl ammatory response to injury or infection [62].…”
Section: Central Pathways: the Infl Ammatory Refl Exmentioning
confidence: 92%
“…In the lungs, pharmacological α7nAChR stimulation correlated with reduced lipopolysaccharide (LPS)-induced neutrophil recruitment [61]. Collectively, these studies suggest that either by electrical or chemical intervention, this infl ammatory refl ex pathway can be modifi ed to modulate the infl ammatory response to injury or infection [62].…”
Section: Central Pathways: the Infl Ammatory Refl Exmentioning
confidence: 92%
“…In the lungs, pharmacological α7nAChR stimulation correlated with reduced lipopolysaccharide (LPS)-induced neutrophil recruitment [61]. Collectively, these studies suggest that either by electrical or chemical intervention, this inflammatory reflex pathway can be modified to modulate the inflammatory response to injury or infection [62]. …”
Section: The Biological Perspective: Non-visual Effects Of Lightmentioning
confidence: 99%
“…In fact, the identification of TLRs at the end of the last century boosted the research in innate immunity and bacterial infections and definitely broadened our understanding of underlying mechanisms and pathways involved. The entire field is certainly beyond the scope of this article and Sylvia Knapp therefore focused on clinical aspects, explains currents therapeutic trials and highlights the role of TLRs in recognition of endogenous danger signals.Van Westerloo describes in his article the role of the vagus nerve upon activation of the innate immune response during infection or injury [2]. Recently, a neural circuit involving the vagus nerve has been identified that controls the inflammatory response in a reflex-like manner.…”
mentioning
confidence: 99%
“…Van Westerloo describes in his article the role of the vagus nerve upon activation of the innate immune response during infection or injury [2]. Recently, a neural circuit involving the vagus nerve has been identified that controls the inflammatory response in a reflex-like manner.…”
mentioning
confidence: 99%